A Case Report on ECIRS for the Complex Retrieval of an Encrusted Ureteric Stent in a Renal Transplant Recipient. - Muhammad Fairuz Shah Bin Abd Karim (Journal of Clinical and Health Sciences, 2026)
We present the case of a 30-year-old male renal transplant recipient who defaulted follow-up for ureteric stent removal. Several months post-transplant, he presented with worsening renal function. Imaging revealed a severely encrusted stent with graft hydroureteronephrosis. Multiple endourological attempts at removal were unsuccessful. During one attempt, the stent fractured, leading to urosepsis and hemodynamic instability. Urgent graft nephrostomy was performed. Following stabilization, endoscopic combined intrarenal surgery (ECIRS) enabled complete removal of all stent fragments. A persistent ureteric stricture was subsequently managed with a Boari’s flap reconstruction. The patient recovered fully with stable graft function and resolution of hydronephrosis on follow-up imaging. This case highlights the challenges of managing neglected ureteric stents in transplant recipients, particularly the anatomical and immunological considerations. A staged approach is critical to preserving graft function and achieving successful outcomes.